Academic integrity policies of five top universities in Malaysia - Zangenehmadar, Samaneh; Tan, Bee Hoon; Abdullah, Mardziah Hayati; Yong, Mei Fung (Universiti Putra Malaysia Press, 2015)
The purpose of this study is to investigate integrity policies of five top public universities in Malaysia. To collect the data relevant policies as well as any other related information about plagiarism management processes were retrieved and downloaded from the university websites. Then the policies were coded and analyzed based on Australian university integrity policies of five core elements of exemplar. The results indicated that policies of Universities A, B, and D are easy to locate and access. Universities A, B, and C apply both punitive and educative approaches to address plagiarism. They also provide a clear outline of the responsibility for academic integrity which must be borne by the students and the staff of the universities. The study highlights the exemplar of five core elements in Malaysian university integrity policies and may serve as reference for universities interested in developing a holistic integrity policy.